2006
DOI: 10.1515/revneuro.2006.17.5.469
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Plasticity and Motor Activity Studied with Transcranial Magnetic Stimulation

Abstract: For decades cortical representations of the parts of the body have been considered to be unchangeable. This view has changed radically during the past 20 years using new tools designed to study plasticity in the adult human brain. Transcranial magnetic stimulation (TMS) is a valuable non-invasive technique for exploring the ability of the motor cortex to change during motor skill acquisition. Results obtained with TMS in neurological patients as well as in normal subjects demonstrate that cortical plasticity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 86 publications
4
17
0
Order By: Relevance
“…Such abnormal muscle co-activation pattern in the paretic limb may be due to an abnormal increase in the overlap of cortical representation for elbow and shoulder joint/muscles. Evidence for cortical overlap of joint/muscles representations has been provided by results in both animals (Clark et al, 1988; Godde et al, 1996; Gribble and Scott, 2002; Hoffer et al, 2005; Rathelot and Strick, 2006) and human subjects (Cramer et al, 2003; Devanne et al, 2006; Godde et al, 1996; Marconi et al, 2007; Melgari et al, 2008; Schabrun and Ridding, 2007; Singh and Scott, 2003; Tyc and Boyadjian, 2006). It has been suggested that such overlaps may be the neural substrate to create a wide variety of functional muscle synergies (Melgari et al, 2008; Rathelot and Strick, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Such abnormal muscle co-activation pattern in the paretic limb may be due to an abnormal increase in the overlap of cortical representation for elbow and shoulder joint/muscles. Evidence for cortical overlap of joint/muscles representations has been provided by results in both animals (Clark et al, 1988; Godde et al, 1996; Gribble and Scott, 2002; Hoffer et al, 2005; Rathelot and Strick, 2006) and human subjects (Cramer et al, 2003; Devanne et al, 2006; Godde et al, 1996; Marconi et al, 2007; Melgari et al, 2008; Schabrun and Ridding, 2007; Singh and Scott, 2003; Tyc and Boyadjian, 2006). It has been suggested that such overlaps may be the neural substrate to create a wide variety of functional muscle synergies (Melgari et al, 2008; Rathelot and Strick, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…However, current knowledge indicates "the neuro-muscular system from brain to muscles is plastic" [145]. Finally, compared to the huge knowledge about biological effect of exercises in healthy neuro-muscular system (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Innumerable studies show that muscle activity but also muscle hypoactivity have multiple effects [155] on: (1) motor controlneurophysiological effects [29,30,38,44,161], and spinal and cortical neuroplasticity [1,126,145,157,158] (recently face motor cortex plasticity has also been reviewed [131]); (2) hemodynamics (see refs. below); (3) histological parameters (phenotypic conversion and change of size/number -i.e., hypertrophy/hyperplasia, respectively -of muscle fibres, and exercise-induced capillary angiogenesis -see refs.…”
Section: Healthy Musclementioning
confidence: 99%
“…TMS is based on Faraday's law of electromagnetic induction, by which electrical activity in the brain tissue can be influenced by the magnetic field, thereby inducing electrical current that depolarizes neurons [2,9]. The application of rTMS generates clear effects on a range of measures of brain function and has become an important research tool due to its potential application as a clinical treatment for a variety of neurological and psychiatric disorders, for instance, depression [2,[10][11].…”
Section: Introductionmentioning
confidence: 99%